The Transformation of Organizational Culture in Promoting the Adoption of Sustainable Digital Practices in Smes: A Systematic Literature Review and Meta-Analysis - Muhammad Mudjib Musta’in; Achmad Muzajjad (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to explore the impact of organizational culture on the adoption of sustainable digital practices in small and medium sized enterprises (SMEs) and to compare these practices with traditional sustainability approaches. Using a systematic literature review (SLR) and meta-analysis approach, this research identifies and synthesizes findings from various relevant studies, providing an in-depth understanding of the relationship between organizational culture and digital transformation. The findings indicate that an organizational culture that supports innovation and collaboration plays a crucial role in enhancing SMEs’ ability to adopt digital technologies, which in turn improves their sustainability and competitiveness in the market. The practical implications of this study include recommendations for SMEs to develop an adaptive and responsive organizational culture toward technological changes. This can be achieved through employee training, digital skill development, and the creation of a work environment that fosters participation and creativity. The study highlights the importance of integrating cultural and technological aspects within digital transformation strategies, which can strengthen SMEs’ positioning in facing global challenges. This research provides an original contribution by addressing the gap in the literature regarding the relationship between organizational culture and sustainable digital practices, particularly in the context of SMEs. Thus, it not only enhances academic understanding but also offers practical guidance for business practitioners to optimize their digital transformation efforts.